Plexin-Semaphorin Signaling Modifies Neuromuscular Defects in a Drosophila Model of Peripheral Neuropathy - Grice, Stuart J.; Sleigh, James N.; Zameel Cader, M. (Frontiers in Molecular Neuroscience, 2018)
Dominant mutations in GARS, encoding the ubiquitous enzyme glycyl-tRNA synthetase (GlyRS), cause peripheral nerve degeneration and Charcot-Marie-Tooth disease type 2D (CMT2D). This genetic disorder exemplifies a recurring paradigm in neurodegeneration, in which mutations in essential genes cause selective degeneration of the nervous system. Recent evidence suggests that the mechanism underlying CMT2D involves extracellular neomorphic binding of mutant GlyRS to neuronally-expressed proteins. Consistent with this, our previous studies indicate a non-cell autonomous mechanism, whereby mutant GlyRS is secreted and interacts with the neuromuscular junction. In this Drosophila model for CMT2D, we have previously shown that mutant gars expression decreases viability and larval motor function, and causes a concurrent build-up of mutant GlyRS at the larval neuromuscular presynapse. Here, we report additional phenotypes that closely mimic the axonal branching defects of Drosophila plexin transmembrane receptor mutants, implying interference of plexin signalling in gars mutants. Individual dosage reduction of two Drosophila Plexins, plexin A (plexA) and B (plexB) enhances and represses the viability and larval motor defects caused by mutant GlyRS, respectively. However, we find plexB levels, but not plexA levels, modify mutant GlyRS association with the presynaptic membrane. Furthermore, increasing availability of the plexB ligand, Semaphorin-2a, alleviates the pathology and the build-up of mutant GlyRS, suggesting competition for plexB binding may be occurring between these two ligands. This toxic gain-of-function and subversion of neurodevelopmental processes indicate that signalling pathways governing axonal guidance could be integral to neuropathology and may underlie the non-cell autonomous CMT2D mechanism.